Comportamento pró-ambiental de servidores terceirizados participantes de programas de gestão socioambiental em órgãos públicos federais. - Ferreira, Maria Augusta Soares de Oliveira (2022)
Human behavior and lifestyle sometimes contribute to the accelerated degradation of the environment. In the field of psychology, an area known as environmental psychology, it investigates the impact of mannature relationships in search of solutions to preserve the environment, encouraging the adoption of proenvironmental behaviors. These are understood as protective behaviors and promoters of a healthy environment. The Social Cognitive Theory (SCT), which supports the present study, has been widely used to understand these behaviors and has contributed to the improvement of socio-environmental management. In particular, we will adopt the concepts of self-efficacy and moral agency to understand the expression of this type of behavior in the different life contexts of civil servants. While the concept of moral agency refers to moral standards as stimulators or inhibitors of certain behaviors, the concept of self-efficacy refers to the belief in the ability to act in accordance with these standards in search of desired results. From this perspective, both concepts will influence the adoption of pro-environmental behavior. The behaviors investigated concern the saving of water and energy, and the correct disposal of waste in work, domestic and other contexts. That said, the objective of this study was to investigate the relationship between proenvironmental behavior, self-efficacy and moral agency, of outsourced workers participating in socioenvironmental management programs of two federal public agencies in the city of Recife. The study followed a mixed design (QUAN-QUAL), in which an environmental self-efficacy scale was used, applied to 122 outsourced workers and, among these, 31 cleaning and pantry workers were interviewed, as they are servers that deal more directly with natural resources. In the quantitative phase, a predominantly male profile was identified (63.31%), with complete secondary education (67.2%), with a family income between 0 and 2 minimum wages (83.6%). Most had received training (76.2%) for about eight months (66.7%). As for the functions, it was found that the majority provided internal (30.33%) and external (26.23%) administrative support, followed by activities related to cleaning (21.31%), to the pantry (8.20%), and maintenance technicians (5.74%). No significant differences were found in relation to the perception of self-efficacy in the face of sociodemographic variables. In the qualitative phase, based on a thematic content analysis, the actions of saving, reusing, properly discarding, guiding, reporting and complaining in the face of environmental problems or anti-environmental behavior witnessed by servers were highlighted. The analysis of the interviews revealed the practice of pro-environmental behaviors in work, family and other contexts, permeated by a high sense of effectiveness in self-regulation processes and applying the SCT for the analysis of these behaviors was perceived as a contribution to socio-environmental public management. Recommendations were made for the improvement of the programs, especially management strategies focused on the perception of self-efficacy, as well as greater investment in adequate infrastructure to promote pro-environmental behaviors.